Computed tomography in chronic inflammatory bowel disease. Issue 5 (1st May 1997) - Hyer, W; Beattie, R M; Walker-Smith, J A; McLean, A
Abstract : In children with complicated inflammatory bowel disease, conventional ultrasound imaging may not define the extent of extraluminal disease and the involvement of other viscera. Three children with chronic inflammatory bowel disease are presented, where computed tomography was well tolerated and provided valuable information on extraluminal disease, involvement of other organs, and the state of the bowel wall and mesentery. In children in whom ultrasound examination is inconclusive or limited by gas or tenderness, computed tomography can provide important information that may determine clinical management.